Peru’s emerging craft-brewing industry and its implications for tourism - Duarte Alonso, Abel; Kok, Seng; O'Shea, Michelle (Wiley-Blackwell, 2020)
While the body of research on craft beer production, consumption, and tourism is growing, some regions, such as Latin America, where beer products are also popular, have received much less attention. This study addresses this knowledge gap, exploring craft breweries in Peru, where in recent years gastronomy has gained significant momentum. In doing so, Porter’s three generic competitive strategies and the resource-based view (RBV) frameworks are considered. Differentiation and focus strategies, coupled with firm resources, including symbiotic relationships between restaurateurs and craft breweries, camaraderie, and continuous partnership development emerged as key competitive factors, with key implications for tourism development.